Mengelola Pembelajaran dengan Metode Hypnoteaching - Hakim, Lukmanul; Hariawan, Rudi (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2017)
The number of teaching methods or strategies becomes an indication that none of the best or most powerful teaching methods are to be used in the learning process. In the end all came back to the teacher himself. Therefore, educators must have insight, understanding, and mastering various teaching methods, so they can choose and be able to apply it in their best way. Hypnoteaching as a teaching method that is quite unique does require adjustment, especially its appearance that gives the impression of making the hypnoteaching method is considered less rational in the world of education, because that in this paper, will be discussed about the management of learning with hypnoteaching methods, concepts, history and strategy learning to enrich the insight of teachers’ teaching skills amidst the rapid development and progress of science and technology.